The idea of Brazilian fashion in the press: decolonial reflections in the transatlantic space (Revista de Ensino em Artes, Moda e Design, 2024)
The article aims to analyze the speeches published in the press in the 19th century and the first half of the 20th century about the idea of Brazilian fashion. To do this, we take a historical perspective to understand how transformations in the national and international context contributed to the development of this narrative and, consequently, the creation and dissemination of clothing characterized as national. Supported by the decolonial perspective, the publication of criticisms of the transatlantic circulation of European fashions, especially French fashion, is highlighted, and then the elements considered necessary for the creation of a national fashion are presented. With this, we can observe that in addition to the geographical aspect, the dissemination of the idea of Brazilian fashion in the press also depended on a set of external and internal factors. Thus, although the decolonial notion only appeared in the second half of the 20th century, we see how criticisms of foreign dependence and demands for fashion that represents Brazilian identity were already addressed in the press.
Keywords: press; brazilian fashion; decolonial studies